Familial aggregation of chronic diarrhea disease (CDD) in rhesus macaques (Macaca mulatta). Issue 3 (1st November 2013) - Kanthaswamy, Sree; Elfenbein, Hanie A.; Ardeshir, Amir; Ng, Jillian; Hyde, Dallas; Smith, David Glenn; Lerche, Nicholas
<x xml:space="preserve">Abstract</x> Chronic diarrheal disease (CDD) is a critical problem for breeders of captive rhesus macaque (Macaca mulatta), as it results in significant levels of morbidity and death annually. As with other inflammatory disorders, CDD is thought to be caused by environmental and/or genetic factors. Although correspondence between the characters defined as Mendelian by pedigree or segregation analysis and functional genes is difficult to establish, such analyses provide essential entry points into understanding CDD in captive bred rhesus macaques. To investigate the familial aggregation of CDD in captive rhesus macaque, we performed pedigree, segregation and heritability analyses on genealogical data from 55 severely affected individuals (probands) through whom relatives with a history of CDD were ascertained from routine computerized colony records comprising vital and demographic statistics of 10, 814 rhesus macaques. We identified 175 rhesus macaques with CDD and estimated its incidence as approximately 2% in the colony. The disease strongly clustered in eight multi‐generation pedigrees. Inspection of the pedigrees, segregation analysis and heritability estimate of CDD suggest that susceptibility to the disease is under strong genetic control. Identification of the locations of susceptibility genes in the rhesus macaque genome could facilitate the reduction of their frequency in captive breeding facilities. Am. J. Primatol. © 2013 Wiley Periodicals, Inc.